Trends and Projections in Income Replacement during Retirement - Smith, James P. (Journal of Labor Economics, 2003)
This article calculates retirement income–replacement rates for all labor market cohorts across the last 25 years and describes the changing contributions made by private pensions, social security, and assets. The factors on which replacement rates are sensitive include position in the income distribution, the use of after‐tax instead of pretax incomes, the changing family composition of households between their pre‐ and postretirement years, and differential underreporting of income by age. The debate about reforming the U.S. retirement income system starts from a base where the current system offers high income‐replacement rates for most households, especially low‐income households.